Respuesta :

S1NGH

Answer:

[tex]\frac{13}{7}[/tex]

Step-by-step explanation:

→ State the slope formula

( y₂ - y₁ ) ÷ ( x₂ - x₁ )

→ Substitute in the values

( 7 - -6 ) ÷ ( 4 - -3 )

→ Simplify

[tex]\frac{13}{7}[/tex]

Answer:

slope = [tex]\frac{13}{7}[/tex]

Step-by-step explanation:

Calculate the slope m using the slope formula

m = [tex]\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex]

with (x₁, y₁ ) = (- 3, - 6) and (x₂, y₂ ) = (4, 7)

m = [tex]\frac{7-(-6)}{4-(-3)}[/tex] = [tex]\frac{7+6}{4+3}[/tex] = [tex]\frac{13}{7}[/tex]